Use of Herbal Medicine among Hypertensive Patients in the Ga East District, Greater Accra. - Asante, A. A. (University of Ghana, 2012)
Hypertension is a growing public health problem in Ghana and Africa as a whole. In recent times hypertensive patients have resorted to the use of herbal medicine. The objective of this study is to investigate the use of herbal medicine among hypertensive patients in Ga East district. This study assessed the extent of use, factors associated with the use of herbal medicine, and the type of herbal medicines being used among hypertensive patients in Ga East district. This was a cross-sectional study carried out at two hypertension clinics of the Ga East district. Two hundred and three participants were randomly selected from May 2012 to June 2012. Data was collected using an interview-administered structured questionnaire. From the study the prevalence of herbal medicine use was 66%. The most common herbal medicines the respondents used were dandelion, moringa, bitter leaves, garlic, dawadawa, soboro, prekese and other herbal concoctions. Patients who believed that hypertension can lead to complications were more likely to use herbal medicine (OR=3.80, 95% CI 1.66-8.70).Those who had information from relatives and friends were also likely to use herbal medicine (OR= 3.00 95% CI 1.56-5.76). The belief that hypertension can be cured was also a risk factor for the use of herbal medicine (OR= 2.70 95% CI 1.32-5.49) as well as the level of hypertension (OR= 1.68 95% CI 1.15-2.47). University of Ghana http://ugspace.ug.edu.gh iii Dandelion and moringa are the most used herbs. The study concludes that perception about severity (knowledge about the complications of hypertension and level of HPT), perception of susceptibility (belief that hypertension is curable), perception of benefits and cost (Control of blood pressure), and cues for action (Information from relatives) can help predict whether a hypertensive patient will take herbal medicine or not.
Keywords: Herbal Medicine; Hypertension